Peran Peran Education Management Information System (EMIS) dalam Transparansi dan Akuntabilitas Data di Ponpes Tahfizul Qur’an - Ansori, Ahmad; Mandela, Rahmat Yoza; Agustinus, Fahrullah; Adawiyah, Rahel; S., Salwa Riswanda (Universitas Cokroaminoto Yogyakarta, 2025)
This study aims to examine the role of the Education Management Information System (EMIS) in realizing data transparency and accountability at the Tahfizul Qur'an Islamic Boarding School in Sungai Pinang, identify operational obstacles in its implementation, and determine strategies and future prospects in strengthening EMIS-based governance towards the principles of good governance. Using a qualitative approach, the study was conducted through direct observation and in-depth interviews with the head of the Islamic boarding school, EMIS operators, and administrative staff. Data collection referred to semi-structured guidelines to capture experiences, challenges, and perceptions of the system. Data analysis was carried out through data reduction, presentation, and drawing conclusions based on the Moleong model. The results indicate that EMIS is effective in increasing transparency through open data access and strengthening accountability through verified digital documentation. However, its implementation is hampered by five problems: system disruptions during unannounced maintenance, limited operator competency, weak internal coordination in document collection, inadequate technological infrastructure, and minimal outreach and mentoring from the Ministry of Religious Affairs. These findings confirm that the success of EMIS depends not only on system availability, but also on institutional capacity, infrastructure support, and synergy between central policies and field realities. Thus, EMIS has the potential to become an effective governance instrument if these operational constraints can be addressed systematically and sustainably.